2022
DOI: 10.1111/raq.12648
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of aquaculture sustainability through ecological intensification in China

Abstract: Aquaculture is the fastest growing food production industry in terms of annual production growth and has become a significant contributor of essential macro-and micronutrients to the diets of the global population. [1][2][3] Increasing the consumption of farmed aquatic food products over land-raised animal meat could potentially reduce the amount of land required for growing feed crops for a global population expected to reach nine billion people by 2050. 4 However, there is a great deal of uncertainty in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…It is independently reported that large‐scale IFA threatens not only the coastal and inland water ecosystems but also results in losses linked with high fish concentration. There are also concerns about whether it will be possible to provide sufficient feed for all the new IFAs being built 13 . Mutual injuries and other stress factors increase the incidence of disease vectors and slow fish growth 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is independently reported that large‐scale IFA threatens not only the coastal and inland water ecosystems but also results in losses linked with high fish concentration. There are also concerns about whether it will be possible to provide sufficient feed for all the new IFAs being built 13 . Mutual injuries and other stress factors increase the incidence of disease vectors and slow fish growth 14 .…”
Section: Introductionmentioning
confidence: 99%
“…There are also concerns about whether it will be possible to provide sufficient feed for all the new IFAs being built. 13 Mutual injuries and other stress factors increase the incidence of disease vectors and slow fish growth. 14 Despite all this, investors around the world still consider a lot of untapped potential in IFA.…”
Section: Introductionmentioning
confidence: 99%
“…However, potential increase in aquaculture production is limited by environmental challenges and resource constraints (Klinger and Naylor, 2012;FAO, 2020). Integrated multi-trophic aquaculture, which involves the cultivation of fed species (e.g., finfish or shrimps fed sustainable commercial diets) with extractive species (e.g., suspensionand deposit-feeders, or seaweeds or other aquatic vegetation), is considered an effective solution to meet the demands of aquaculture production and achieve sustainable aquaculture development (Chopin et al, 2001;Abreu et al, 2011;Dong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The fish-lighting complementary PV power mode is aligned with the concept of green development. Furthermore, research has shown that the integration of aquaculture and solar power generation can improve the economic efficiency and employment level of aquaculture systems (Dong, et al, 2022), and play an important role in aquaculture's ability to resolve energy demands (Li, et al, 2020b). Consequently, the "Fishery-PV Integration" mode has broad developmental prospects.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, aquaculture has developed rapidly, but its level of intensification is low and mainly based on extensive farming (Dong, et al, 2022). One important reason is that intelligent fishery facilities and equipment consume a large amount of electricity, which increases the cost of farming.…”
Section: Introductionmentioning
confidence: 99%